The Diagnostic Value of Multimodal Neurophysiological Assessment in Chemotherapy-Induced Peripheral Neuropathy: A Prospective Diagnostic Accuracy Study - Xiaohe Shi; Kaixin Li; Yinliang Liu (Discovery Medicine, 2026)
Background: Chemotherapy-induced peripheral neuropathy (CIPN) is a common and dose-limiting toxicity associated with platinum and taxane based anticancer agents. However, early detection remains challenging due to the lack of objective assessment tools. This study aims to compare the dynamic changes in multimodal neurophysiological parameters before and after chemotherapy, assess the diagnostic value of conventional nerve conduction studies (NCS), sympathetic skin response (SSR), and the N9 wave tibial nerve somatosensory evoked potential (tSEP) in detecting CIPN, and explore the utility of combined testing in identifying subclinical neuropathy.Methods: Forty cancer patients undergoing platinum - or taxane-based chemotherapy and 40 healthy controls were prospectively enrolled. NCS, SSR, and tSEP were administered before chemotherapy and after its completion, or three weeks following the onset of neurological symptoms. CIPN positivity was defined using a composite endpoint (NCI-CTCAE grade ≥1 combined with electrophysiological deterioration), and subclinical CIPN was characterized as NCI-CTCAE grade 0 with abnormal electrophysiological findings. Changes in parameters before and after chemotherapy were statistically compared. The sensitivity, specificity, and area under the curve (AUC) of each parameter for diagnosing CIPN were calculated. Additionally, the detection rates of different testing strategies for subclinical CIPN were compared.Results: After chemotherapy, 28 patients (70.0%) met the composite endpoint criteria for CIPN. In addition, 5 patients (12.5%) were classified as having subclinical CIPN. Post-chemotherapy analysis revealed significant declines in the sensory conduction velocity (SCV) and sensory nerve action potential (SNAP) of the medial and lateral plantar nerves, prolongation of SSR latency and reduction of SSR amplitude, as well as a decrease in tSEP N9 wave amplitude (all p < 0.001). Individually, upper limb SSR amplitude exhibited the highest diagnostic efficacy (AUC = 0.844, 95% confidence interval (CI): 0.721–0.967), while the medial plantar nerve SCV showed a specificity of 92% (AUC = 0.798). A logistic regression model incorporating these two parameters improved the AUC to 0.881 (95% CI: 0.772–0.990). In an exploratory analysis of five patients with subclinical CIPN, SSR alone detected all cases, while the combination of NCS and SSR also achieved complete detection (McNemar’s exact test, p = 1.00). However, due to the extremely small sample size, this finding should be interpreted as preliminary and hypothesis-generating, warranting validation in larger studies.Conclusion: Multimodal neurophysiological assessment effectively delineates the pattern of nerve fiber damage in CIPN. The combination of SSR amplitude and medial plantar nerve SCV shows promising diagnostic performance in an exploratory analysis, but these findings require validation in independent cohorts using a truly independent reference standard.